The Impact Of Digital Transactions In The Reconciliation Process And Preparation Of Financial Reports Of Culinary Msmes In Palembang City - Widarti Widarti; Yeni Alfiana; Della Wandira (UNIVED Press, 2024)
The aim of this research is to determine The Impact Of Digital Transactions In The Reconciliation Process And Preparation Of Financial Reports Of Culinary Msmes In Palembang City. The method used is The descriptive analysis method is a statistical technique that describes and describes data as it is collected, without trying to draw any generalizations or conclusions. In this research, the data that has been collected will be classified based on relevant categories, such as online sales, online payments, online deliveries, reconciliation processes and financial reports. Data will be analyzed descriptively to provide a clear picture. This involves the use of descriptive statistics such as frequencies, percentages, and means. This research was conducted on culinary MSMEs in the city of Palembang. This research processed data from 30 respondents, namely women dominated with a percentage (67%). Respondents with an age range of 41-50 years dominate with a percentage (36%). Then the level of education dominates SMA/SMK and D3/S1/S2/S3 with the same percentage, namely (15%).